Improving EFL Students’ Speaking Skill in Junior High School through Cake Application - Sheviona Charisma (Retain: Journal of Research in English Language Teaching, 2026)
Speaking is the one most important skill for students, especially in English. In this digital era, teachers can use many websites as learning tools to increase students' confidence, for example the use of the Cake application. This research aims to implement the use of cake applications as a learning media for eighth grade students through recounting text as learning material. This research employed a quasi-experimental design that involved 64 samples (The sample was divided into two groups, namely the experimental and control groups consisting of 32 participants each). After the instrument data (post-test and pre-test) was collected, the data were analyzed using independent sample t-test. The findings showed a clear difference between the experimental and control groups. The result, which was two-tailed, had a value of 0.014, which is below the standard significance level of 0.05. This means that the improvement in the experimental group, after using the Cake application, is statistically significant. The study concluded that the use of Cake applications in recount text materials can improve students' speaking skills including increasing vocabulary and students' confidence in learning English.